The role of self-acceptance in civic engagement among academic students from Poland, Lithuania, and Croatia during the Covid-19 pandemic - Marciniak, Mateusz; Jaskulska, Sylwia; Jankowiak, Barbara; Janiūnaitė, Brigita; Horbačauskienė, Jolita; Gasparovic, Slaven; Glavak Tkalić, Renata (Biuletyn Socjoterapeutyczny, 2025)
The aim of research was to explore the relationship between self-acceptance (SA) and civic engagement (CE) among academic students (N= 1,362) from Poland, Lithuania and Croatia. Binomial logistic regression and subgroup analyses (by gender, country, study degree, and study field) were performed. The results indicated that the students with the lowest levels of SA exhibited the lowest levels of CE. In addition, men were less likely to present high CE compared to women, students from Lithuania were less likely to be highly civically engaged in comparison to those studying in Poland, and students of the natural sciences and humanities were less likely to have a high level of CE than those studying social sciences. The study underscores the critical role of self-acceptance in promoting civic engagement among young adults. During health crises such as a pandemic, it is essential to encourage student involvement in activities that support local and global communities, particularly focusing on individuals with the lowest levels of self-acceptance.